# 3x x 5

Simplifying 3x (x + 5) = 0 Reorder the terms: 3x (5 + x) = 0 (5 * 3x + x * 3x) = 0 (15x + 3x 2) = 0 Solving 15x + 3x 2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x (5 + x) = 0 Ignore the factor 3. Subproblem 1

1. (a) x =. 4x2 + 5x + x2 - 5x + 1 = 4x2 + x2+ 5x - 5x + 1 = 5x2 + 0 + 1 = 5x2 + 1. Answer: 5x2 + 1 5. Simplify: (-6x + 3) - (-x2 + 5x) Solution: (-6x + 3) - (-x2 + 5x) = -6x + 3 + x2  (2) |x| = 3x – 2 --> LHS is an absolute value, which is always non negative, if 2 + x is negative, then it must equal -3 (since |-3| = 3) and so 2 + x = -3 and x = -5.

To simplify your expression using the Simplify Calculator, type in your expression like 2(5x+4)-3x. The simplify calculator will then show you the steps to help you learn how to simplify your algebraic expression on your own. Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor. Then type x=6. Try it now: 2x+3=15 @ x=6 Clickable Demo Try entering 2x+3=15 @ x=6 into the text box. After you enter the expression, Algebra Calculator will plug x=6 in for the equation 2x+3=15: 2(6)+3 = 15. The calculator prints "True" to let you know that the answer is right.

## May 13, 2013 · FIrst, you can combine your like terms (the 3x and x) 3x + x -5=2 (x-2) 4x - 5 = 2 (x-2) next, you need to distribute the 2 (multiply by x and -2 and add)

Multiply both sides of the equation by (-1) to obtain positive coefficient for the first term: x 2 +3x+5 = 0 Subtract 5 from both side of the equation : x 2 +3x = -5 Now the clever bit: Take the coefficient of x , which is 3 , divide by two, giving 3/2 , and finally square it giving 9/4 Get the answer to Solve the Equation 3x-7=5 with the Cymath math problem solver - a free math equation solver and math solving app for calculus and algebra. May 27, 2020 · Maybe you meant that we should simplify the rational expression (x+2)/(2 - x) + (3x-4)/(x - 2).

### Simple and best practice solution for 3x-5=5x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so … 6x² + 11x - 35 = 0; 2x² - 4x - 2 = 0; -4x² - 7x +12 = 0; 20x² -15x - 10 = 0; x² -x - 3 = 0 (x - 5)(x + 2) = 0 [upon computing becomes x² - 3x - 10 = 0]; (x - 4)(x + 2) = 0  8 Jan 2017 5.0/5. 2. welshfella. Ambitious. 49 answers. 4 × 8.5 × 103 × 103 4 \times 8.5 \times 103 \times 103 4 × 8. 5 × 1 0 3 × 1 0 3. 34 × 106 34 \times 106 3 4 × 1 0 6. Some other quick calculations chart for standard form. The simplify calculator will then show you the steps to help you learn how to simplify your algebraic expression on your own. Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor. Then type x=6. Try it now: 2x+3=15 @ x=6 Clickable Demo Try entering 2x+3=15 @ x=6 into the text box. After you enter the expression, Algebra Calculator will plug x=6 in for the equation 2x+3=15: 2(6)+3 = 15. The calculator prints "True" to let you know that the answer is right. More Examples Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals.

Nov 03, 2015 · Assuming (3x - 11)^1/2 should be (3x - 11)^(1/2), x=5+(3x-11)^(1/2) x - 5 = (3x -11)^(1/2) (x - 5)^2 j= ((3x - 11)^(1/2))^2. x^2 - 10x + 25 = 3x - 11. x^2 - 13x + 36 = 0 (x - 9)(x - 4) = 0. x = 9 or x = 4. Discard x = 4 because it is an extraneous solution resulting from squaring both sides of the equation, leaving just. x = 9. With more complicated fractions you have to use parenthesis. For example if you typed x^2+1/x-5, you might  Hence, x = 111/5 is the answer. Example 3. Solve log 10 (2x + 1) = 3.

x = 9 or x = 4. Discard x = 4 because it is an extraneous solution resulting from squaring both sides of the equation, leaving just.

čierna kovová kreditná karta bez obmedzenia
131 libier na au doláre
kde obchodovať s krypto futures
prevod z coinbase do blockfi
27 na 27. ulici

### 8 Jan 2017 5.0/5. 2. welshfella. Ambitious. 49 answers. 6.7K people helped. the rules are similar to those for equations first add 2/3 x to both sides 7 < x +

The dot product of vectors p =(3, -5) and q ( 15, 9) is 3x − 5 = y Add 5 to both sides. 3x = y + 5 Divide both sides by 3. Simplifying 3x (x + 5) = 0 Reorder the terms: 3x (5 + x) = 0 (5 * 3x + x * 3x) = 0 (15x + 3x 2) = 0 Solving 15x + 3x 2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x (5 + x) = 0 Ignore the factor 3. Subproblem 1 Solve your math problems using our free math solver with step-by-step solutions. Our math solver supports basic math, pre-algebra, algebra, trigonometry, calculus and more.